A review on modelling and analysis of 7 level multi level inverter with various circuit configurations - Karri, Nanajee; Pandian, Alagappan (International Journal of Electrical and Computer Engineering (IJECE), 2022)
For the last decade, the multilevel inverters became popular and are extensively using for a high power and medium voltage applications. The multi level inverter (MLI) concept has been introduced with lot of topologies like diode clamped type, Flying capacitor type and cascaded H-Bridge (CHB) type multi level inverter. The major objective of the multilevel inverter is to get higher voltage levels with lower switching components. Out of available topologies, the cascaded H-Bridge type has been focused more. But, the cascaded H-Bridge type requires more and more number of switches. In this review paper, three topologies have been discussed and compared for seven level output voltage. The total harmonic distortion (THD) is also measured. The comparison table is also shown. The work is done by using MATLAB/SIMULINK software.